The Effect of Metalaxyl Application on Anatomical Structure of Tomato Lycopersicon esculentum Mill. - İlkay Öztürk; Nedret Tort; Necip Tosun (Journal of Agricultural Sciences)
In this study, a fungicide as known Megasil %35 Metalaxyl were pulverized on tomato plants Lycopersicon esculentum Mill. in greenhouses in Fethiye, in Muğla. Then the likely effects of this fungicide on anatomical structures of plants were examined. The fungicide applications were carried out to tomato according to farmer of tomato in greenhouses in this area at doses 5 g/ 12 l water and two fold 10 g/ 12 l water of these doses. In the application of Metalaxyl, some anomalies in the anatomical structure of the plant have been observed. All fungicide applications resulted in decreasing in cross section cell layer thickness of leaf, stem and fruit. In addition, deformations in mesophyll cells of leaves, assimilating palisade paranchyma cells of stem and mesocharp cells of fruit were found as well. This situation may indirectly cause a negative effect in the amount and quality of the yield